Manejo de envases de agroquímicos y el cumplimiento de la normativa legal en el sitio Guabal, Parroquia Quiroga - Pinargote Anchundia, Gari Israel (2023)
The objective of this research was to evaluate the management of plastic waste for agricultural use, in compliance with Ecuadorian legal regulations. 4 activities were carried out; a survey of the inhabitants of the site consisting of 8 questions to assess their knowledge about plastic waste for agricultural use and the understanding they have regarding Ecuadorian legal regulations, revealing that the inhabitants of the Guabal site use agrochemicals in their crops, but lack information and support from the authorities, as well as a specific place for waste and are usually abandoned in the open air. A verification matrix of environmental regulations was applied to evaluate compliance with it, finding that the inhabitants of the Guabal site do not comply with the established. A Guide of good environmental practices was developed for the proper management of plastic waste for agricultural use and the consequences that these have for the environment and the health of farmers when it is handled incorrectly. After this, the respective socialization of the guide of good environmental practices was carried out to the inhabitants of the Guabal site in a comprehensive manner which evidenced the interest of the inhabitants on the actions and equipment necessary for the proper management of plastic waste for agricultural use, in order to avoid future health problems.